2002
DOI: 10.1098/rstb.2001.0887
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in the dendrite

Abstract: In neurons, many proteins that are involved in the transduction of synaptic activity and the expression of neural plasticity are specifically localized at synapses. How these proteins are targeted is not clearly understood. One mechanism is synaptic protein synthesis. According to this idea, messenger RNA (mRNA) translation from the polyribosomes that are observed at the synaptic regions provides a local source of synaptic proteins. Although an increasing number of mRNA species has been detected in the dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 93 publications
(119 reference statements)
2
44
0
Order By: Relevance
“…Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999). Further, Roche et al (2001) have shown that the C-terminus of NR2B subunit is sufficient for rapid internalization of the NMDA receptor.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999). Further, Roche et al (2001) have shown that the C-terminus of NR2B subunit is sufficient for rapid internalization of the NMDA receptor.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Stimulation of synapses results in locally increased protein synthesis, which requires cytoplasmic polyadenylation and CPEB (Si et al 2003a). This local translation is required for the late phase of LTP, an electrophysiological, cellular correlate of memory (Nguyen et al 1994;Frey et al 1988;Liu and Schwartz 2003; for reviews, see Wells et al 2000;Richter 2001;Tang and Schuman 2002). Four isoforms of CPEB are found in the hippocampus (Wu et al 1998;Theis et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the molecular machinery necessary for translation activity in spines and dendritic shafts (Steward and Levy, 1982;Tang and Schuman, 2002;Asaki et al, 2003), and the observed translocation of polyribosomes from dendritic shafts to spines following tetanic stimulation, which also increases the number of spines that contain polyribosomes (Ostroff et al, 2002), suggest that local protein synthesis may play an important role in synaptic plasticity. Accordingly, an overall increase in protein synthesis was observed in experiments where patterned synaptic stimulation was paired with muscarinic receptor activation with carbachol, in hippocampal slices (Feig and Lipton, 1993).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%
“…The presence in dendrites of the machinery necessary for protein synthesis, together with the mRNA for AMPAR subunits, suggests that local synthesis of AMPAR subunits regulates local receptor abundance and composition (Steward and Levy, 1982;Kacharmina et al, 2000;Tang and Schuman, 2002;Asaki et al, 2003;Ju et al, 2004;Grooms et al, 2006). Accordingly, chronic activity blockade increases the synthesis of GluR1 in dendrites, and acute activation of group I metabotropic glutamate receptors (mGluRs) or acute depolarization with KCl increases the synthesis of both GluR1 and GluR2 (Ju et al, 2004).…”
Section: Expression Of Amparsmentioning
confidence: 99%